Assessment of Power Generation Potential By Using Combination of Non Woody Biomass Species Namely Gulmohar And Cassia Tora Separately With Coal Briquette in Four Varying Ratios – A Review: Exploring the Potential of Non Woody Biomass Species for Power Generation (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Biomass is more economically viable for almost all the continents in the world. Biomass is a carbonaceous material and provides both the thermal energy and reduction for oxides, where as other renewable energy sources can meet our thermal need only. There are various types of renewable energy sources available such as solar, wind, hydropower, biomass energy etc. Biomass power generation in India is an industry that attracts investments of over Rs.600 crores every year, generating more than 5000 million units of electricity and yearly employment of more than 10 million man-days in the rural areas.